Analisis Model PBL dengan Media Canva terhadap Hasil Belajar Siswa Pendidikan Pancasila Kelas Tinggi SD - Annisa Asmi; Adrias Adrias; Salmaini Safitri Syam (Universitas Maritim AMNI Semarang, 2025)
One of the conditions for achieving learning objectives is the achievement of satisfactory grades from students. Educators must be able to use learning models so that students are active not passive. The learning model is a learning process from start to finish. The model that educators can apply is the Problem Based Learning (PBL) model. The PBL model is one of the learning models where students are given real problems and students must be able to find solutions by finding a way out. The implementation of the learning model must be accompanied by media. The learning media that can be used is Canva. Canva is an audio-visual based learning media. Canva utilization can be applied to higher grade Pancasila Education. The application of the PBL model with Canva media in Pancasila Education for classes IV, V and VI found learning problems that still apply teacher centered methods and lack of media which makes learning outcomes low. The research method used is a qualitative method with literature study data collection. The results showed that the use of the PBL model with Canva-based learning media for Pancasila Education in high grades can make student learning outcomes change and improve. Changes and improvements can occur because in the PBL model learning is not teacher centered but student centered which makes students have to think critically, creatively and actively in solving a given problem.